2007
DOI: 10.1007/s00213-007-0705-3
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine and prazosin slow the rhythm of head movements during focused stereotypy induced by d-amphetamine in rats

Abstract: The results show that clozapine diminished the rhythm and vigor of d-amphetamine-induced stereotyped head movements but, at the same time, lengthened the duration of the expression of the stereotypy. alpha1 antagonism is a likely contributor to the rhythm-modulating effects of clozapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The concept and applications of this instrument for measurement of tremor, locomotor activity and stereotypy in rodents were described in the USA and pending international patents (USA Patent no. 6,601,010), as well as in published research [24][25][26][27][28][29].…”
Section: Force Plate Actimetersmentioning
confidence: 96%
See 2 more Smart Citations
“…The concept and applications of this instrument for measurement of tremor, locomotor activity and stereotypy in rodents were described in the USA and pending international patents (USA Patent no. 6,601,010), as well as in published research [24][25][26][27][28][29].…”
Section: Force Plate Actimetersmentioning
confidence: 96%
“…Focused stereotypy ''was defined by a quantitative score that combined a direct instrumental measure of spacial confinement with the variance in the vertical force oscillations, that the rat exhibited within that space'' [27][28][29]. This parameter aimed to reflect repetitive head movements of frequency between 6.5 (7.5) and 12 Hz induced by dopaminomimetics in ''one-place'' [27,29] However, this parameter did not differentiate between various forms of stereotypy (e.g., sniffing, licking, gnawing, biting). The plate was divided into a 16 by 16 grid of 256 squares to calculate the percentage of time and the force variance while the animal was in each square.…”
Section: Force Plate Actimetersmentioning
confidence: 99%
See 1 more Smart Citation
“…These episodes of excessive drug intake can be modeled in the laboratory by giving subjects unlimited-access to a drug during 12- to 24-h test sessions. During these sessions, animals will exhibit high levels of drug intake that are associated with a loss of circadian patterns of motor activity, a dysregulation of homeostatic autonomic functions, and acute withdrawal symptoms upon session termination (Mutschler and Miczek, 1998; Tornatzky and Miczek, 2000; Fowler et al, 2007). Recently, Smith et al (2011b) reported that exercise reduces cocaine intake during a 23-h period of unlimited drug access.…”
Section: The Effects Of Exercise On Drug Self-administration: Cocainementioning
confidence: 99%
“…In rodents, it has been reported that administration of drugs of abuse, including AMPH and METH, induces multiple behavioral responses, such as increased locomotor activity (Porrino et al 1984;Salahpour et al 2008), stereotypy (Battisti et al 2000;Fowler et al 2007), and disrupted prepulse inhibition of acoustic response (Sills 1999;Peleg-Raibstein et al 2008). p-Hydroxyamphetamine (p-OHA), an AMPH and METH metabolite, has been shown to have a number of pharmacological actions, including causing abnormal behaviors such as those induced by drugs of abuse (Simpson 1980;Dougan et al 1986;Arai et al 1990; Kaminskas et al 2002).…”
Section: Introductionmentioning
confidence: 97%